White Unwed Mother; the Adoption Mandate in Postwar Canada - Andrews, Valerie J (Demeter Press, 2018)
In postwar Canada, having a child out-of-wedlock invariably meant being subject to the adoption mandate.Andrews describes the mandate as a process of interrelated institutional power systems which, together with socio-cultural norms, ideals of gender heteronormativity, and emerging sociological and psychoanalytic theories, created historically.